The Transnational Construction and Maintenance of Digital Feminist Media Activism: Engagement Practices in the Global South and North - Mariana Fagundes-Ausani (Gender a Výzkum)
The article observes, from a transitional perspective, how feminist activists appropriate digital spaces to produce informative content about gender equity and how they organise themselves to maintain feminist media projects in terms of content production and public access to this information. The research focuses on analysing three Brazilian publications (AzMina, Lado M, and Think Olga) and three French ones (Georgette Sand, Les Glorieuses, and Madmoizelle). The global North-South category is mobilised to propose a dialogue between feminist journalism practices in Brazil and France, using both countries because they are important players on the international geopolitical scene. I use theories of gender studies and feminism as bibliographical support and draw on the theoretical framework of symbolic interactionism correlated with social worlds from a Beckerian perspective to trace the conventions and forms of cooperation, interaction, and negotiation used by the journalists and contributors to these publications. The methodology is based on in-depth interviews with actors who participate to different degrees in the composition of the world (of feminist me-dia activism) - content producers, support teams, and audiences - and direct observation of the practices developed by participants in these spaces to enable a multi-site comparison and provide transnational evidence of the ways in which digital feminist media work.